2019
DOI: 10.1080/15384101.2019.1678965
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA ANRIL knockdown relieves myocardial cell apoptosis in acute myocardial infarction by regulating IL-33/ST2

Abstract: Objective: To investigate the role of lncRNA ANRIL in the modulation of myocardial cell apoptosis in acute myocardial infarction (AMI). Methods: AMI mice model was established, and lncRNA ANRIL, IL-33 and ST2 expressions were detected by quantitative real-time polymerase chain reaction (qRT-PCR) or western blot. The apoptosis of myocardial cells was detected by TUNEL assay. RNA pull-down and RNA immunoprecipitation (RIP) assays were used to confirm the interaction between lncRNA ANRIL and USP17. Results: Compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 28 publications
0
39
0
Order By: Relevance
“…Kcnq1ot1 could be used as a prognostic indicator to determine left ventricular function (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Kcnq1ot1 could be used as a prognostic indicator to determine left ventricular function (33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal expression of ANRIL is associated with vascular endothelium injury and proliferation, migration, and apoptosis of VSMCs; which also contribute to mononuclear cell adhesion and proliferation ( 104 , 105 ). ANRIL knockdown induced cardiomyocyte apoptosis in acute MI by regulating IL-33/ST2 or Akt ( 106 , 107 ). Enhanced expression of ANRIL and suppressed expression of miR-181b, which was inhibited by ANRIL, were recorded in CAD populations and confirmed ANRIL as an independent risk factor ( 108 ).…”
Section: Predicted Lncrnas Based On Available Evidencementioning
confidence: 99%
“…In contrast to the immunomodulation effect of IL-18 which can stimulate Th1 cells to secrete a variety of cytokines and promote the proliferation of Th1 cells, IL-33/sST2 can regulate Th1/Th2 balance by promoting Th2 anti-inflammatory immunity and inhibiting Th1 immune response. 9 Emerging studies have revealed that IL-33/sST2 is closely correlated with cardiovascular diseases, autoimmune and nervous system diseases, 10–12 yet its role in the nervous system remains poorly understood. Some studies have demonstrated that serum IL-33 has a protective effect against stroke through anti-inflammatory and can improve the prognosis of stroke.…”
Section: Introductionmentioning
confidence: 99%